Segmenting Cruise Consumers by Motivation for an Emerging Market: A Case of China - Jiao, Yue; Hou, Yating; Lau, Yui-yip (Frontiers in Psychology, 2021)
After around four decades of fast growth, the cruise industry has become the most profitable and dynamic segments in the entire global leisure and tourism sector. Behind this growth is a significant shift in the profile of the cruise consumers/passengers/tourists, with growth rates twice as fast as those of other types of tourists. China has become a strategic emerging market for the global cruise industry, quickly developing their cruise reception business and holding about 10% of the market share of global cruisers. In this paper, we examine and categorize various travel motivations of Chinese cruise tourists by means of a questionnaire via factor analysis, mean analysis, and K-cluster analysis. The results of the study indicate that Chinese cruise tourists are primarily encouraged to participate in cruise tourism by the motivational dimensions of family leisure/relaxation, natural and cultural exploration, bond/communication, social respect, tourism shopping, and cruise-promotion information sources. The strongest motivations for Chinese cruise tourists were found to be family leisure/relaxation and natural/cultural exploration. We identify four types of cruisers using K-means cluster method. We find that for all cruiser demographics, leisure/relaxation is the most important motivational factor. Based on these results, we propose some specific solutions for expanding the customer pool in the Chinese cruise market.